Transforming Local Wisdom: Qualitative Exploration of Purun Straw Adoption in an Effort to Reduce Plastic Emissions - Fatwa Nur'aini; Sovia Husni Rahmia; Syarifuddin Syarifuddin; M. Ridha Ilhami; Sigit Triyono (The Kalimantan Social Studies Journal, 2025)
This study examines the process of transforming local wisdom by using purun straws as an environmentally friendly alternative toplastic straws in an effort to mitigate carbon emissions. Through a qualitative approach with in-depth interviews, participatoryobservations, and document analysis, this study explores how local communities are adapting traditional knowledge about theutilization of purun plants into contemporary solutions to global environmental problems. The findings show that the adoption ofpurun straws has not only succeeded in reducing plastic waste but also empowering local economies, preserving cultural practices,and creating sustainable environmental awareness. Factors supporting success include community involvement, local governmentpolicy support, and the integration of traditional knowledge with modern technology. Key challenges include standardizingproduction, scaling up, and price competition with plastic products. The results highlight the importance of a local wisdom-basedapproach in addressing global environmental problems, providing a model that has the potential to be applied to other contexts andcommunities with appropriate adaptations.